Health education strategies to improve handwashing and waste disposal in Klakah Village - Rizki, Lailina Aminatur; Leksono, Amin Setyo; Batoro, Jati (Jurnal Pembangunan dan Alam Lestari, 2026)
Sanitation challenges, including low compliance with handwashing practices and improper waste disposal, remain critical public health concerns in Klakah Village. This study aimed to evaluate the effectiveness of integrated health education strategies using both print and digital media, and to examine their association with handwashing and waste disposal behaviors. A descriptive-analytic study with a cross-sectional design was conducted involving 84 households selected through stratified random sampling. The intervention consisted of health education delivered through posters, leaflets, digital presentations, and short videos to enhance community awareness and behavioral change. Data were collected through structured observations, interviews, and questionnaires, and analyzed using bivariate statistical tests to assess the relationships between educational exposure, attitudes, habits, and sanitation-related behaviors. The results revealed a statistically significant yet weak positive association between attitudes, habitual practices, and sanitation behaviors. Households exposed to combined print and digital educational media demonstrated more favorable attitudes toward handwashing and waste management, as well as improved behavioral practices compared to baseline conditions. Despite the modest strength of the associations, the findings suggest that multi-modal health education strategies can contribute to incremental improvements in sanitation behavior at the household level. This study underscores the importance of integrating traditional and digital communication approaches to enhance the effectiveness of public health interventions, particularly in rural settings with limited sanitation infrastructure. Strengthening community engagement and ensuring sustained educational efforts are essential to achieving long-term behavioral change and improving environmental health outcomes.